2010
DOI: 10.1128/jvi.01571-09
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Mammalian Orthoreovirus Proteins to Cytoplasmic Factory-Like Structures via Nonoverlapping Regions of μNS

Abstract: Virally induced structures called viral factories form throughout the cytoplasm of cells infected with mammalian orthoreoviruses (MRV). When expressed alone in cells, MRV nonstructural protein NS forms factory-like structures very similar in appearance to viral factories, suggesting that it is involved in forming the structural matrix of these structures. NS also associates with MRV core particles; the core proteins 2, 1, 2, 3, and 2; and the RNA-binding nonstructural protein NS. These multiple associations re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
106
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(113 citation statements)
references
References 50 publications
6
106
0
Order By: Relevance
“…Inmammalian genera of the family reoviridae, μNS is sufficient to form VFs (viral factories) [24], and it recruits σNS to VFs [27]. The μNS protein acts as a scaffold to recruit viral core surface proteins [25], while σNS binds preferentially to ss-RNA and ss-DNA [26,27]. In members of the genus fijivirus such as RBSDV, nonstructural protein RBSDV P9-1 is important for the functioning of the relative proteins in Vps during viral morphogenesis [28], RBSDV P9-1 self-associates into aggregate formations and preferentially binds ss-RNA molecules [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Inmammalian genera of the family reoviridae, μNS is sufficient to form VFs (viral factories) [24], and it recruits σNS to VFs [27]. The μNS protein acts as a scaffold to recruit viral core surface proteins [25], while σNS binds preferentially to ss-RNA and ss-DNA [26,27]. In members of the genus fijivirus such as RBSDV, nonstructural protein RBSDV P9-1 is important for the functioning of the relative proteins in Vps during viral morphogenesis [28], RBSDV P9-1 self-associates into aggregate formations and preferentially binds ss-RNA molecules [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Specific regions within the NS protein that are required for recruitment of the viral core and six other MRV proteins to VFs and for forming VFs have previously been identified (6,7,9,10,12) (Fig. 1A).…”
Section: Construction Of Plasmids Expressing the Tc Tag From Within Tmentioning
confidence: 99%
“…We separated the TC-NS mutants based on previously identified functions of NS to include the N-terminal third (aa 1 to 221), the central third (aa 222 to 470), and the C-terminal third (aa 471 to 721). Previous studies have found that the NS N-terminal third is both necessary and sufficient to bind virus proteins NS, 2, 1, 2, and 2, the C-terminal third is necessary and sufficient to bind 3, form VFs, and bind cellular clathrin, and the central third has been implicated in recruiting cellular protein Hsc70 to VFs (6,7,9,10,12,26,27). To examine the impact of the introduced TC-NS mutations, we cotransfected cells with each pTC-NS mutant or wild-type pT7-M3 along with plasmids expressing each of the other six virus proteins individually.…”
Section: Construction Of Plasmids Expressing the Tc Tag From Within Tmentioning
confidence: 99%
See 1 more Smart Citation
“…This minimal factory-forming region has two predicted coiled-coil domains linked by a putative zinc hook and followed by a short C-terminal tail (26). The first one-third of NS (aa 1 to 221) has been identified as a scaffold for the recruitment of the viral proteins 1, 2, 2, 2, and NS; in contrast, the RNA-dependent RNA polymerase (RdRp), 3, interacts with the C-terminal minimal factory-forming region (5,27,28). So far, no function has been elucidated for the middle portion of NS (aa 222 to 470).…”
mentioning
confidence: 99%